На крыльях любви: роман / Уитни Килмер - Килмер Уитни (Панорама романов о любви, 1998)
Экземпляры: Ф. 10 (20200626) / Инвентарный номер: 47898 / Цена: 15.00 / Сис.шифр: 84(4 Вел) / Авт.знак: К 39 / ГРНТИ: 17.82 / ББК: 84(4 Вел)